Analisis Pengaruh Kualitas Pelayanan Terhadap Kepuasan Nasabah BMT UGT Sidogiri Cabang Bangkalan - Nisa, Khoirun (Universitas Negeri Surabaya, 2020)
AbstractThis study ams to see how the effect of service quality on customer satisfaction, a case study in the district of bangkalan.This quantitative research used a sample of 64 customer of BMT Sidogiri in Bangkalan Regency branch. To obtain the data, the researcher used a closed-ended questionnaire. The analysis data used simple linear regression analyzed test and partial test. This study found the results of the t-test were at a significant value with a magnitude of 0.00 so that it was greater than 0.05 which meant that the variable quality of service had a significant influence and a good direction on customer satisfaction. While the results of the determinant coefficient test (R2) were at the value of 0.145 which meant that service quality variables had an effect of 14.5 percent on customer satisfaction. The result of this study indicate that service quality has a very positive and significant effect on customer satisfaction.